Pharmacotherapies for stimulant use disorder and co-occurring attention deficit hyperactivity disorder: protocol for a systematic review and a meta-analysis - Oliva, Henrique N. P.; Pulido-Saavedra, Alejandra; Paredes-Naveda, Alisson; Forselius, Emerson; Potenza, Marc N.; Jegede, Oluwole O.; Angarita, Gustavo A. (Frontiers in Psychiatry, 2025)
BackgroundStimulant use disorder (StUD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. This comorbidity complicates treatment and worsens clinical outcomes. Despite the high prevalence, shared vulnerability and clinical relevance of this comorbidity, evidence on effective pharmacotherapies among individuals with this dual diagnosis remains limited.Materials and methodsThis systematic review protocol is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement and will include randomized controlled trials involving adults with comorbid StUD (cocaine, amphetamines, or methamphetamines) and ADHD. The following databases will be searched: PubMed, Embase, Scopus, and Web of Science. Covidence will be used to support independent screening and data extraction. Two reviewers will independently screen studies (title/abstract and full text). One author will extract data, which will be independently verified by a second reviewer. Quality assessment of included articles will be assessed using the Cochrane Risk of Bias instrument, and certainty of the evidence for each outcome will be assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) methodology. Primary outcomes include duration of continuous abstinence, odds of stimulant-negative urine samples, ADHD symptom changes, and medication adverse events. Where feasible, meta-analyses will be conducted using random-effects models.Significance and disseminationThis review will synthesize existing evidence on the efficacy of pharmacotherapies (stimulants and non-stimulants) for individuals with co-occurring StUD and ADHD. The results of this study will likely inform clinical practice by evaluating outcomes such as reduction in stimulant use and abstinence, and improvement in ADHD symptoms. Findings will be disseminated through peer-reviewed publication and presentations to reach both clinical and academic audiences.Systematic review registrationPROSPERO, CRD420250655356.